Calcium Signaling Pathways in Physiological Regulation and Disease Development: A Comprehensive Review - Khairullah, Aswin Rafif; Kurniasih, Dea Anita Ariani; Maruf, Ilma Fauziah; Pratama, Bima Putra; Sukmanadi, Mohammad; Ansori, Arif Nur Muhammad; Mustofa, Imam; Wardhani, Bantari Wisynu Kusuma; Ahmad, Riza Zainuddin; Martindah, Eny; Mulyati, Sri; Yulianti, Wita; et al. (Trends in Sciences, 2026)
Calcium ions (Ca²⁺) are universal signaling molecules that play a central role in physiological processes, including muscle contraction, hormone secretion, gene regulation, energy metabolism, and neurotransmission. This review aims to integrate the SOCE-MCU-CaM axes to provide a systems-level view of Ca²⁺ regulation from the plasma membrane to the ER/SR, mitochondria, and nucleus in physiology and pathology. The Ca²⁺ signaling pathway encompasses ion transport by Ca²⁺ pumps and Na⁺/Ca²⁺ exchangers, ion flow through plasma-membrane channels and the endoplasmic/sarcoplasmic reticulum (ER/SR), and interactions with binding proteins such as calcineurin and calmodulin (CaM), which trigger downstream programs including NFAT, CREB, and MAPK. Maintenance of cytosolic and mitochondrial Ca²⁺ homeostasis depends on pathways such as the mitochondrial calcium uniporter (MCU) and store-operated calcium entry (SOCE) via STIM1/Orai1; their coordinated action links Ca²⁺ transients to metabolism and gene control. Dysregulation of Ca²⁺ signaling contributes to chronic diseases, including neurodegeneration (Alzheimer’s, Parkinson’s), cardiovascular disease (heart failure, arrhythmia, hypertension), cancer (breast, lung, colorectal), and metabolic/endocrine disorders (diabetes and insulin resistance). Unchecked Ca²⁺ accumulation or pathway imbalance promotes oxidative stress, apoptotic activation, impaired energy metabolism, and cellular dysfunction, while mutations in Ca²⁺-related genes alter cardiac contractility and other physiological regulation. Therapeutic approaches include Ca²⁺-channel modulation, targeting STIM1, Orai1, and MCU, and epigenetic strategies that leverage Ca²⁺’s influence on gene expression, with the goal of restoring network-level Ca²⁺ equilibrium and improving cell function. A clearer understanding of Ca²⁺ mechanisms and pathway cross-talk will support the development of more precise and effective interventions. HIGHLIGHTS Homeostatic Ca²⁺ signaling integrates SOCE (STIM1-Orai1), VGCCs, SERCA/PMCA, and mitochondrial MCU to coordinate excitation-secretion, metabolism, and gene programs. Organellar Ca²⁺ dysregulation underlies neurodegeneration, cardiac remodeling/arrhythmia, endocrine-metabolic dysfunction, and cancer progression. Calmodulin-driven transduction (CaM-calcineurin/NFAT and CaMK axes) links Ca²⁺ oscillations to transcriptional remodeling and disease-specific vulnerabilities. Mitochondrial Ca²⁺ uptake via the MCU complex couple’s bioenergetics to redox signaling; imbalance promotes ROS, defective mitophagy, and cell death. Therapeutic avenues span SOCE inhibitors and selective Ca²⁺ channel blockers to mitochondria-targeted MCU modulators with disease-tailored strategies. Research priorities: Cell-type-resolved Ca²⁺ mapping with advanced imaging and multi-omics to identify precision targets along SOCE-MCU-CaM pathways. GRAPHICAL ABSTRACT